CPT1A/2-Mediated FAO Enhancement—A Metabolic Target in Radioresistant Breast Cancer - Han, Shujun; Wei, Ryan; Zhang, Xiaodi; Jiang, Nian; Fan, Ming; Huang, Jie Hunter; Xie, Bowen; Zhang, Lu; Miao, Weili; Butler, Ashley Chen-Ping; Coleman, Matthew A.; Vaughan, Andrew T.; et al. (Frontiers in Oncology, 2019)
Tumor cells including cancer stem cells (CSCs) resistant to radio- and chemo-therapy must enhance metabolism to meet the extra energy demands to repair and survive such genotoxic conditions. However, such stress-induced adaptive metabolic alternations, especially in cancer cells that survive radiotherapy, remains unresolved. In this study, we found that CPT1 (Carnitine palmitoyl transferase I) and CPT2 (Carnitine palmitoyl transferase II), a pair of rate-limiting enzymes for mitochondrial fatty acid transportation, play a critical role in increasing fatty acid oxidation (FAO) required for the cellular fuel demands in radioresistant breast cancer cells (RBCs) and radiation-derived breast cancer stem cells (RD-BCSCs). Enhanced CPT1A/CPT2 expression was detected in the recurrent human breast cancers and associated with a worse prognosis in breast cancer patients. Blocking FAO via FAO inhibitor or by CRISPR-mediated CPT1A/CPT2 gene deficiency inhibited radiation-induced ERK activation and aggressive growth and radioresistance of RBCs and RD-BCSCs. These results revealed that switching to FAO contributes to radiation-induced mitochondrial energy metabolism, and CPT1A/CPT2 is a potential metabolic target in cancer radiotherapy.